ANGELA MURRAY’S EXPERIENCE OF PASSING UP AS WHITE IN JESSIE REDMON FAUSET’S PLUM BUN - Ratna Asmarani (LITERA, 2018)
The aim of this paper is to analyze the experience of Angela Murray, the female mulatto protagonist, when she finally decides to pass as a white person in Plum Bun, a novel written by Jessie Redmon Fauset. Considering that the focus of analysis is a female, the feminist literary criticism is used as the main framework. The contextual method of analysis is supported by some concepts concerning skin color and passing. The result shows that Angela goes through three periods of her existence. At first she plays with her skin color by passing temporarily as white with her mulatto mother. Then she decides to pass permanently as white and moves to a different state in which she is involved in an intimate relationship with a wealthy racist white man and humiliatingly hurts her younger black sister, her black female acquaintance, and the man she actually loves. Finally she confesses her true racial heritage and makes amends to the people she has hurt and finds the happiness she has sought so far.Keywords: skin color, passing as white, racist, racial heritage PENGALAMAN ANGELA MURRAY MENJADI KULIT PUTIH DALAM PLUM BUN KARYA JESSIE REDMON FAUSET AbstrakTujuan dari makalah ini adalah untuk mengkaji pengalaman Angela Murray, protagonis mulato perempuan, ketika ia akhirnya memutuskan untuk ‘passing’ atau menjadi kulit putih dalam novel berjudul Plum Bun karya Jessie Redmon Fauset. Mengingat bahwa fokus analisis adalah seorang perempuan, kritik sastra feminis digunakan sebagai kerangka utama. Metode analisis kontekstual didukung dengan konsep tentang warna kulit dan ‘passing’. Hasil kajian menunjukkan bahwa Angela melewati tiga periode keberadaan. Awalnya ia bermain-main dengan warna kulitnya dengan ‘passing’ sementara sebagai orang kulit putih bersama ibunya yang mulato. Kemudian ia memutuskan untuk ‘passing’ sebagai orang kulit putih secara permanen dan pindah ke negara bagian lain di mana ia terlibat dalam hubungan intim dengan laki-laki kulit putih kaya yang rasis dan melukai hati adik perempuannya yang berkulit hitam, kenalan perempuan yang berkulit hitam, dan laki-laki yang sebenarnya dicintainya. Akhirnya ia mengakui warisan rasialnya dan menebus kesalahan pada orang-orang yang telah disakitinya dan menemukan kebahagiaan yang selama ini dicarinya.Kata kunci: warna kulit, ‘passing’ sebagai kulit putih, rasis, warisan rasial